Flow and heat transfer analysis of water-based copper nanofluid over a nonlinearly stretching sheet: a numerical approach. Issue 1 (31st December 2022) - Swain, Kharabela; Mishra, Swetapadma
ABSTRACT: Specifically, copper nanoparticles are utilised in various fields like biomedicine, drugs, bioengineering, hereditary designing, catalysis, beauty care products, etc. The present study warrants the 3D magnetised flow and heat transfer of water-based copper nanofluid past a nonlinearly stretching sheet in presence of thermal radiation and exponential space-based heat source (ESHS). With the help of apposite match transformations, the governing partial differential equations (PDEs) are converted to coupled nonlinear ordinary differential equations (ODEs) and are solved numerically using the shooting method with the aid of MATLAB software. The presence of magnetic field and porous matrix leads to reduce the momentum boundary layer and may be treated as the control mechanism in technological applications. An asymptotic variation of rate of heat transfer coefficient is marked in heating of the plate with higher power index for heat source, volume fraction and Biot number.